2004
DOI: 10.1523/jneurosci.0600-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine, through the Extracellular Signal-Regulated Kinase Pathway, Downregulates CD4+CD25+Regulatory T-Cell Activity: Implications for Neurodegeneration

Abstract: Fighting off neuronal degeneration requires a well controlled T-cell response against self-antigens residing in sites of the CNS damage. The ability to evoke this response is normally suppressed by naturally occurring CD4 ϩ CD25ϩ regulatory T-cells (Treg). No physiological compound that controls Treg activity has yet been identified. Here, we show that dopamine, acting via type 1 dopamine receptors (found here to be preferentially expressed by Treg), reduces the suppressive activity and the adhesive and migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
170
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(188 citation statements)
references
References 50 publications
(49 reference statements)
10
170
1
3
Order By: Relevance
“…These differences in the decrease of EAE severity and in disease onset observed in D5RKO mice and WT mice transferred with D5RKO DCs may suggest that D5R signaling in cell types other than DCs is involved in the progression and development of this autoimmune disease. In this regard, Kipnis et al (52) have described that Tregs express type I DARs, and stimulation of these receptors attenuates the suppressive activity of Tregs. Thus, absence of D5R in Tregs could favor the suppressive activity of these cells and thereby contribute to decreased EAE manifestation observed in D5RKO mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in the decrease of EAE severity and in disease onset observed in D5RKO mice and WT mice transferred with D5RKO DCs may suggest that D5R signaling in cell types other than DCs is involved in the progression and development of this autoimmune disease. In this regard, Kipnis et al (52) have described that Tregs express type I DARs, and stimulation of these receptors attenuates the suppressive activity of Tregs. Thus, absence of D5R in Tregs could favor the suppressive activity of these cells and thereby contribute to decreased EAE manifestation observed in D5RKO mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding expression of DA receptors (DARs) in immune cells, these receptors have been found not only in cells of the innate immune response such as dendritic cells (DCs), NK cells, macrophages/monocytes and granulocytes (19)(20)(21) but also in cells of the adaptive immune response such as B cells, CD8 + T cells, and CD4 + T cells (22)(23)(24)(25)(26)(27)(28)(29)(30). Despite being lesser studied than in human T cells, DARs expression has also been described in murine T cells (26,31). Pharmacological evidence obtained from a group of studies performed with human T cells has suggested that among five DARs described so far (D1R-D5R), both type I (D1R and D5R) and type II (D2R, D3R, and D4R) contribute to the regulation of T cell function.…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 99%
“…This latter cell type, in particular CD4 + T cells, are most relevant since it was recently shown that the key role of A 2A Rs in attenuating peripheral tissue damage from ischemiaYreperfusion injury is due to the activation of A 2A Rs in CD4 + T cells [322]. Since the depletion of CD4 + YCD25 + regulatory T cells has been shown to promote survival of neurons after brain insults [323], in a manner regulated by metabotropic receptors such as dopamine D 1 receptors [324], it would be interesting to test if A 2A Rs might affect this particular population of T cells to control brain injury. However, the urgent need remains to provide a logical explanation for the fundamentally opposite effects of A 2A Rs in cell death involving inflammatory reactions in the brain and in the periphery.…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionmentioning
confidence: 99%